KEMITRAAN SEKOLAH DAN ORANG TUA DALAM PENANAMAN KEDISPLINAN IBADAH SISWA SMA NEGERI 5 YOGYAKARTA - Nurfiyani Dwi Pratiwi (Jurnal Pendidikan Agama Islam)
Nurfiyani Dwi Pratiwi. Partnership Schools And Parents In Students’ Worship Disciplines Education. Yogyakarta: Islamic Teaching Department ofTarbiya and Teaching Faculty UIN Sunan Kalijaga Yogyakarta. This study aims to determine the form of partnership schools and parents in educate worship discipline of students, as well as factors supporting and inhibiting. This is a qualitative research using approach of Sociology. The results of this research show that 1) Forms of partnerships: teachers and parents meetings, correspondence the school and parents, home visits, parent involvement in school events, associations of parents and teachers, and periodic reports using a books report. 2) The supporting factors: the social competence of teachers, parents’ attention in children’s education, and open access schools. Inhibiting factors: level of education and the work of parents and teachers administrative tasks. Keywords: Partnership, School, Parent, and Worship.